2017
DOI: 10.1007/s00284-017-1256-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of Flagella in the Pathogenesis of Helicobacter pylori

Abstract: This review aimed to investigate the role of Helicobacter pylori flagella on the pathogenicity of this bacterium in humans. Helicobacter pylori is a flagellated pathogen that colonizes the human gastroduodenal mucosa and produces inflammation, and is responsible for gastrointestinal disease. Its pathogenesis is attributed to colonization and virulence factors. The primary function of H. pylori flagella is to provide motility. We believe that H. pylori flagella play an important role in the colonization of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
124
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 140 publications
(131 citation statements)
references
References 83 publications
2
124
0
5
Order By: Relevance
“…The increased levels of ammonia from hydrolysis of urea by urease as well as the metabolites from recruited neutrophils disrupts the gastric epithelium, which synergistically facilitates the development of gastric malignancies [49,50]. In addition, H. pylori possesses four to eight unipolar flagella that are important in bacterial colonization and induce inflammatory response [51]. The flagellar sheath of H. pylori provides the protection of acid-labile flagellar structure from the attack of the acid environment [52].…”
Section: Other Virulence Factorsmentioning
confidence: 99%
“…The increased levels of ammonia from hydrolysis of urea by urease as well as the metabolites from recruited neutrophils disrupts the gastric epithelium, which synergistically facilitates the development of gastric malignancies [49,50]. In addition, H. pylori possesses four to eight unipolar flagella that are important in bacterial colonization and induce inflammatory response [51]. The flagellar sheath of H. pylori provides the protection of acid-labile flagellar structure from the attack of the acid environment [52].…”
Section: Other Virulence Factorsmentioning
confidence: 99%
“…Apart from important flagellar filament proteins, FlaA and FlaB, there are more than 40 proteins that are involved in the flagellar biosynthesis and functioning. 12 It has been found that the function of flagella is regulated by quorum sensing with the help of pheromones such as autoinducer-2 in response to change in the environment. 29,30 The flagella of the H. pylori mainly consists of several structural proteins such as HpaA, FlaA, FlaB, FliD, and FlgK.…”
Section: Motility Of H Pylorimentioning
confidence: 99%
“…There are so many responsible bacterial factors, which may play a role in the persistent infection of H. pylori. They are not limited to motility, presence of flagellar appendages, secretory toxins like Cag‐A, vacuolating cytotoxin A (VacA) toxins that degrade the cellular tissue in contact, and urease that help in survivability in such extreme environments mediated by chemotaxis . Further, their responsive defenses from the host such as receptors like pattern recognition receptors (PRRs), H. pylori ‐specific pathogen‐associated molecular patterns (PAMPs) such as Toll‐like receptor 4 (TLR‐4), DC‐SIGN, and MUC1, etc, also play an important role in the mechanism of competency .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations